Antiquity to modernity in tribal India: continuity and change among Indian tribes (Vol.1) - Dube, S C (ed.) (New Delhi, 1998)
This four-volume study is the outcome of a project undertaken by the ICSSR under the overall leadership of (Late) Prof. S. C. Dube. The study examined the implications of alternative strategies of tribal development so that an informed public opinion could be created to provide necessary inputs into decision making at various levels. The major research areas that have been addressed by the study are: paradigm of tribal development, system of tribal self management, control over resources, and issues in tribal movements. The four volumes that deal with these themes have been titled as: Vol. I: Continuity and Change among Indian Tribes, Vol. II : Tribal Self-Management in North-East India, Vol. III: Ownership and Control of Resources among Indian Tribes, and Vol. IV: Tribal Movements in India. The respective editors of these volumes are: Prof. S. C. Dube, Dr. Bhupinder Singh, Prof. S. N. Mishra and Dr. K. S. Singh. The present volume dealing with the issues of ownership and control over resources addresses the questions of land tenure system and land alienation, agricultural practices including that of shifting cultivation, and dependence on forest resources and also their management. The issues have been studied from the experience of Andhra Pradesh, Bihar, Kerala, Orissa, Tamil Nadu, West Bengal, and the states of North-East.
Keywords: Tribes India